Comparing the performance of traditional non-treponemal tests on syphilis and non-syphilis serum samples. (December 2013) - Gu, Wei-Ming; Yang, Yang; Wang, Qing-zhong; Pan, Bai-shen; Guo, Wei; Wu, Lei; Hu, Wei-zhong; Yang, Sheng; Song, Bin-bin; Zhang, Chun-yan
The goal of the present study was to determine the performance of two traditional non-treponemal tests for syphilis. Syphilis sera ( n = 209) included different stages of disease, and control sera ( n = 247) were from patients with tumours, leprosy, systemic lupus erythematosus, hepatitis, pregnant women and healthy individuals. Treponema pallidum ELISA, Treponema pallidum particle agglutination and rapid treponema-specific tests were used as gold standards. Rapid plasma reagin or toluidine red unheated serum test had a sensitivity and specificity of over 95%. False-negative reactions of rapid plasma reagin and toluidine red unheated serum test were observed mainly in primary and latent syphilis cases, and false-positive reactions were present in systemic lupus erythematosus, hepatitis-infected patients. Overall, both non-treponemal tests had high sensitivities and specificities making the assays attractive as screening tests for syphilis. When examined on WHO reference serum samples and based on lower limits of detection, non-treponemal tests were less sensitive than treponema-specific tests.